Synergies among the Sustainable Development Goals: emphasis on integrating water management and tourism - Nascimento, Regina Célia Macêdo do; Marcon, Priscila; Ghidini, Milena Sciascio; Ribeiro, Roberta Dias de Moraes; Sousa, Fernanda Vale de; Hanai, Frederico Yuri (Sustainability in Debate, 2024)
This study explores the synergies between water management and tourism, analysing the relationship among the Sustainable Development Goals (SDGs). A Focus Group (FG) was used to gather in-depth and unique reflections and generate discussions and interpretations on the topics. The data collected was analysed using Textual Discourse Analysis (TDA), and four categories were thus determined: (i) Dignity, equity and justice, (ii) Socio-biodiversity, (iii) Citizen education, and (iv) Environmentally and socially sustainable economic production. Based on water management and tourism, 170 relationships were found between the SDGs. Six of the 17 goals connected with all the other SDGs, namely SDGs 3, 6, 8, 11, 13 and 17. The dialectic relationship between water conservation and sustainable tourism development is a suitable way to enhance the 2030 Agenda and help build synergies to achieve its goals in an integrated and transdisciplinary way.